The Effectiveness of Swanson's Caring Behavioral Approach on Tuberculosis Treatment Compliance in Families with Children with Tuberculosis at the Children's Clinic of Ende Regional General Hospital - Agnes Ervina Satya Pota; Roswita Victoria Rambu Roku; Margareta Teli; Domianus Namuwali; Febtian Cendradevi Nugroho (Poltekkes Kemenkes Kupang, 2025)
Tuberculosis (TB) in children is a public health challenge that requires special attention, especially due to low levels of family compliance with treatment. This non-compliance risks treatment failure, recurrence, and drug resistance, which are dangerous for children. The role of the family as the primary caregiver is significant in ensuring optimal treatment. Swanson's caring theory, which emphasizes empathy and emotional support, is considered capable of increasing family compliance in accompanying children during TB treatment. This study aims to determine the effectiveness of Swanson's caring behavioral approach on TB treatment compliance in families with children suffering from TB at the Ende Regional General Hospital Pediatric Clinic. The method is quantitative, with a quasi-experimental design featuring a one-group pre-test and post-test design. A total of 30 families were selected using purposive sampling. The intervention was carried out for 12 days through the five dimensions of Swanson's caring, namely maintaining belief, knowing, being with, doing for, and enabling. The measurement instrument uses the Morisky Medication Adherence Scale (MMAS-8) questionnaire to assess treatment adherence before and after the intervention. Data analysis used the Wilcoxon Signed Rank Test. The study showed a significant increase in the level of family adherence in providing TB treatment to children after the Swanson caring intervention (p < 0.05). The application of the Swanson caring behavioral approach was effective in increasing TB treatment adherence in children, so it can be recommended as a family-based intervention strategy to improve the success of TB therapy in children at health facilities.